Identification of The Level of Mastery of Basic Volleyball Techniques For Men of The Cakar Langit Network Club, Padang Lawas Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to map the level of mastery of basic volleyball techniques among male athletes from the Cakra Langit Network Club in Padang Lawas Regency and to formulate training improvement priorities. The study used a quantitative, descriptive cross-sectional approach involving 20 athletes. Measurements were conducted using standardized tests for the serve, underhand pass, overhand pass, and smash, complemented by game-based observations to capture the quality of match execution. Data are presented as percentages of achievement and ability categories. The results indicate that the overall level of mastery of basic techniques is in the moderate category. Specifically, the average achievement for each technique is: underhand pass 55% (moderate), overhand pass 65% (moderate), serve 60% (moderate), and smash 80% (highest). These findings indicate that the technical foundation has been established, but gaps remain in the quality of the first touch. The underhand pass and overhand pass emerged as priority areas for improvement because they determine the quality of subsequent attack transitions. The serve requires increased accuracy and consistency to be more functional as a first attack, while the advantage in the smash needs to be maintained through increased placement accuracy and tempo variation. In conclusion, the club is at a moderate ability level with a need for systematic strengthening in the first touch aspect. Strategic recommendations include target-based training and load progression for passing and serving, the integration of small-sided games/mini-games to encourage transfer to match situations, and regular monitoring every 6–8 weeks. These results are expected to form the basis for developing a focused and effective training program. The limitations of this study include a single club sample, so generalizations require caution; further studies are recommended involving more clubs in Padang Lawas Regency to obtain a comprehensive and representative picture.